Analisis Total Faktor Produksi Yang Mempengaruhi Pertumbuhan Ekonomi Kabupaten Sukoharjo Tahun 2000-2013(Studi Empiris Pada Program Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta) - Mahal, Rizky Bella (2016)
The purpose of this research is to determine the effect of emotional intelligence, self-confidence, learning behavior, and academic culture on the level of understanding of accounting. Data analysis in this study is multiple linear regression analysis. Research populations are 1626 students and samples are 100 students of Accounting Program of Muhammadiyah University of Surakarta. The results showed that: (1) emotional intelligence individually affecting the level of understanding of Accounting at the level 0.05, with sig. emotional intelligence 0.000<0.05; (2) self-confidence individually affecting the level of understanding of Accounting at the level 0.05, with sig. self-confidence 0.000<0.05; (3) learning behavior partial individually affecting the level of understanding of Accounting at the level 0.05, with sig. learning behavior 0.040<0.05; (4) academic culture individually affecting the level of understanding of Accounting at the level 0.05, with sig. academic culture 0.000<0.05; (5) emotional intelligence, self-confidence, learning behavior and academic culture simultaneously affecting the level of understanding of Accounting at the level 0.05, with sig. F 0,000<0,05. (6) Influence can be explained by emotional intelligence, self-confidence, learning behavior and academic culture the level of understanding of Accounting in this research is 93,2%, while 6.8% in addition to the factors described in the model such as learning activities, discipline, and seriousness in studying in campus.